Effects of lower-extremity explosive strength on youth judo athletes adopting different types of power-based resistance training - Huang, Ruiyin; Zhang, Mingyang; Huang, Linjie; Chen, Zilong; Mo, Yong; Gao, Yuhua (Frontiers in Physiology, 2023)
Objective: The present study compared the effects of pneumatic resistance and free weight of 6-week squat training on the performance for young female judo athletes in linear speed and vertical jump. Monitoring data were used to assess the effects and trends of the two resistance types on 70% 1RM weight-bearing. Methods: In a 6 week squat training, 23 adolescent female judo athletes were randomly selected and then divided into the traditional barbell (FW) group and the pneumatic resistance (PN) group according to different resistance types, with 10 in FW group and 9 in PN group actually completed the study. Before and after training, the T-30M, countermovement jump, static-squat jump, and drop jump,DJ-RSI, and maximal strength were assessed. One-Way ANOVA was used to examine the pre-test differences of groups. A 2-factor mixed-model analysis of variance was used to examine the independent effects of group and time ( pre and post) on each dependent measure. Scheffe post hoc comparisons were used to examine the differences. Pre- and post-experimental differences between the two groups were analyzed using independent samples t-tests and magnitude-based inferences (MBI) derived from their p values, and effect statistics were applied to compare the pre- and post- changes exhibited by each group . Results: The PN group outperformed the FW group in terms of maximal power output per training session . After 6 weeks of training, the FW group showed significant increases in vertical jump height and relative strength (CMJ, SJ, DJ), with no significant gains observed in T-30 and maximal strength. the PN group showed significant improvements in maximal strength; however, no significant improvements were observed in the other tests. In addition, there was no significant difference in DJ-RSI between the two groups before and after training. Discussion: At 70% weight bearing, free weight resistance appears to be more conducive to vertical jump growth, while pneumatic resistance appears to be more conducive to maximal strength gains; however, the maximal strength gains from pneumatic resistance may not be well applied to athletic performance. In addition, the body adapts more quickly to pneumatic resistance than to free weight resistance.